2020
DOI: 10.3390/met10070952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Cycling on Wire and Arc Additive Manufacturing of Al-5356 Components

Abstract: Wire and arc additive manufacturing (WAAM) provides a promising alternative to conventional machining for the production of large structures with complex geometry, as well as individualized low quantity components, using cost-efficient production resources. Due to the layer-by-layer build-up approach, process conditions, such as energy input, deposition patterns and heat conduction during the additive manufacturing process result in a unique thermal history of the structure, affecting the build-up properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
(26 reference statements)
3
32
0
Order By: Relevance
“…The strain hardening response of Al-Mg alloys is significant due to the Portevin–Le Chatelier effect [ 42 ]. The excellent properties of 5000-alloys in WAAM materials were frequently demonstrated in later years, including 5087 [ 26 , 43 ], 5183 [ 44 , 45 , 46 , 47 ] and 5356 [ 48 , 49 , 50 ] with commercial feedstock.…”
Section: Aluminum Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The strain hardening response of Al-Mg alloys is significant due to the Portevin–Le Chatelier effect [ 42 ]. The excellent properties of 5000-alloys in WAAM materials were frequently demonstrated in later years, including 5087 [ 26 , 43 ], 5183 [ 44 , 45 , 46 , 47 ] and 5356 [ 48 , 49 , 50 ] with commercial feedstock.…”
Section: Aluminum Alloysmentioning
confidence: 99%
“…The strain hardening response of Al-Mg alloys is significant due to the Portevin-Le Chatelier effect [42]. The excellent properties of 5000-alloys in WAAM materials were frequently demonstrated in later years, including 5087 [26,43], 5183 [44][45][46][47] and 5356 [48][49][50] with commercial feedstock. 6000-series Al-Mg-Si alloys are heat-treatable through precipitation of semicoherent Mg 2 Si β and β -precipitates for increased strength.…”
Section: Aluminum Alloysmentioning
confidence: 99%
“…WAAM is also the AM method used and studied in [2]. This method provides a promising alternative to conventional machining for the production of large structures with a complex geometry, as well as individualized low quantity components using cost-efficient production resources.…”
Section: Contributionsmentioning
confidence: 99%
“…This method provides a promising alternative to conventional machining for the production of large structures with a complex geometry, as well as individualized low quantity components using cost-efficient production resources. The experimental study in [2] describes the effects of thermal cycling on the geometrical and material properties of a WAAM-ed Al-5356 aluminum alloy.…”
Section: Contributionsmentioning
confidence: 99%
“…Martina et al [17] explained the use of the deposition volume to assess bead roughness and investigated the efficiency of various welding techniques and conditions. Köhler et al [18] continuously stacked aluminum wires using WAAM and observed the changes in bead shapes and structures according to the interlayer temperature. As the wire feed and welding speed increased, the layer height decreased and the wall width increased.…”
Section: Introductionmentioning
confidence: 99%